Physicochemical and Organoleptic Characteristics of Snack Bars Combination of Red Bean Flour (Phaseolus vulgaris L.) and Rice Bran Flour with Variation of Roasting Time: Karakteristik Fisikokimia dan Organoleptik Snack Bars Kombinasi Tepung Kacang Merah (Phaseolus vulgaris L.) dan Tepung Bekatul (Rice Brand) dengan Variasi Lama Pemanggangan - Sylvia Astian Wibowowati; Merkuria Karyantina; Akhmad Mustofa (Fakultas Sains dan Teknologi Unisri, 2024)
Red bean flour has a high protein content but low gluten content. The superior nutritional value of rice bran is as a nutrient source that contains a lot of protein and high fiber and also does not cause allergies. The purpose of this study was to determine the effect of roasting time and the best formulation of the combination of red bean flour and rice bran flour in making snack bars that are rich in protein and favored by many consumers. This study used a completely randomized design (CRD) arranged factorially with two factors with the formulation of red bean flour and rice bran flour used were P1 (95:5); P2 (90:10); and P3 (85:15). Roasting time was 50, 40 and 30 minutes. Data analysis used ANOVA with Tukey's further test. The results of chemical and sensory tests significantly influenced the activity of water content, fat content, protein, carbohydrates, color, red bean flavor, bran flavor, hardness and overall liking. However, it was significantly different for ash content, color and overall liking. The best chemical test results were P2T3 (ratio of red bean flour and rice bran flour 90/10 with roasting time of 30 minutes) with the results of carbohydrate 60.74%, protein 10.96%, moisture content 19.01%, fat content 6.79%, and ash content 2.51%. The best sensory test results were P2T3 with color test results 2.98, red bean flavor 2.58, bran flavor 2.32, hardness 1.75, and overall liking 2.77. Snack bars made from red bean flour and rice bran flour have great potential as a high-protein food ingredient.